Pososhkov’s narrow path - Drozdek, Adam (Analecta Cracoviensia, 2012)
The paper presents Ivan Pososhkov (1652-1726). He was a Russian merchant, an entrepreneur, and a landowner. His major work was titled The Book on Poverty and Wealth (1724, published in 1842).The author’s aim is to show Pososhkov’s thought about the schismatics, Protestants, particularly, the Lutherans, and the clergy. One of the parts is dedicated to Pososhkov’s vision of the place of piety in the personal life. All these parts show Pososhkov as a self-appointed teacher whose intention was the defense of traditional Orthodox faith of the official Orthodox Church.